Asymptomatic tiny subcutaneous eruptions in a patient with sarcoid neuropathy the effectiveness of fluorine-18 fluorodeoxyglucose positron emission tomography for targeting safe biopsy sites - Kobayashi, Makoto (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2019)
Background: In sarcoidosis, cutaneous lesions are observed in approximately 25–35% of patients and good sites for diagnostic biopsy when they supposedly contain noncaseating granulomas. Fluorine-18 fluorodeoxyglucose positron emission tomography (FDG PET) is often employed to detect sarcoid lesions in the whole body, but its effectiveness in cutaneous sarcoidosis has been scarcely reported. Case report: A 58-year-old woman presented with a tingling sensation throughout her body. On physical examination, she had bilateral peripheral facial palsy, right-dominant distal muscle weakness in the upper extremities, and decreased or absent tendon reflexes in the four limbs. Skin lesion was not apparent on the initial assessment. However, FDG PET revealed an abnormal tracer accumulation in the lateral side of the right upper arm. Based on this finding, we found a few tiny subcutaneous lumps in the corresponding site, which were slightly palpable and about 2 mm in diameter. Although the FDG PET abnormality was large in comparison with them, the skin around the lumps was subjected to biopsy. Histological examination revealed numerous subcutaneous nodules consisting of noncaseating granulomas. Most of these nodules were too small to be recognized on palpation but probably visible on FDG PET. She was diagnosed as having sarcoid neuropathy and treated successfully with steroids. Conclusions: During the diagnosis of sarcoidosis, FDG PET may detect asymptomatic tiny subcutaneous lesions and provide safe biopsy targets. Moreover, the skin lesions infrequently appear as localized FDG PET abnormalities and may be missed without sufficient attention.